THE APPLICATIVE USE OF PROBLEM SOLVING TECHNIQUE IN TEACHING GRAMMAR - Rahmah Apen (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
This paper is aimed at getting a deep understanding of the process and results in improving grammar mastery in learning English through problem solving technique. It reports the action research involving 30 students of English Education Study Program at Language and Arts Faculty in State University of Padang who took Structure I Subject. The instrument used were questionaire, students’ portofolios, observers’ and reseacher’s journals, pre-test and post-test.The data were analyzed by using descriptive statistics in the form of mean and percentage, and the validity of the data was checked by using triangulation technique.The result shows that (1) The process of using problem solving technique is chalanging, and it makes the students active, thinks critically, improves the students’ learning result, and gradually makes the students become autonomous learners.(2) The result of grammar mastery varied within the three cycles of different instructional activities conducted. The indicators are seen from the pre- to post-test results of each cycle. The results of grammar mastery through classical instructional activities improved from 28.53 to 67.0. In group discussion activities the improvement is from 69.53 to 77.13. Meanwhile, the improvement is seen from 77.06 to 83.23 in pair work instructional activities. Based on  the result,  the learning process through problem solving technique improved the learning result of grammar mastery.